Kepemimpinan Transformasional Untuk Kepala Sekolah Indonesia: Konsep Dan Pengukurannya - Damanik, Enceria; Dewi, Mulia Sari (Pedagogi: Jurnal Ilmu Pendidikan, 2024)
This study explores the application and significance of transformational leadership among school principals in Indonesia. Transformational leadership is considered a pivotal approach for improving the role of principals in driving positive change within educational institutions, impacting teachers, students, and the entire school community. Drawing on transformational leadership theories by Bass and Avolio (2003), the Principal Leadership Questionnaire (PLQ) is adapted specifically for the Indonesian context, measuring dimensions such as Professional Interaction, Participative Decision-Making, Individual Support, Intellectual Stimulation, and Moral Perspective. This instrument has undergone rigorous validation and reliability testing, confirming its suitability for evaluating teachers' perceptions of principals' leadership effectiveness in Indonesian schools. The study highlights the relevance of transformational leadership in addressing challenges unique to Indonesia's educational landscape, including resource limitations and geographic disparities. It concludes by emphasizing the need for principals to adopt transformational leadership to foster a collaborative school climate and calls for further research on adaptive leadership practices within local contexts. Keywords: Transformational Leadership, Principal Leadership Questionnaire, School Principal, Indonesia’s Education, Applied Psychology.